Exploring the antecedent resources and capabilities of strategic corporate social responsibility. Issue 7 (21st September 2020) - Donnelly, Timothy; Wickham, Mark
Abstract : Purpose: While the literature has extolled the desirable outcomes of strategic corporate social responsibility, there is recognised paucity of research concerning its requisite antecedents. Applying the resource-based view (RBV), this paper aims to address the research question: What are the resources and capabilities associated with strategic CSR activities? Design/methodology/approach: A qualitative content analysis of B-Corporation certified firms' annual reports was undertaken to address the research question. Using the global reporting initiative guidelines, the contents of the B-Corporation certified banks were coded against the best-practice CSR benchmarks for economic, social and environmental sustainability reporting. The data were then further scrutinised to detect the resources and capabilities related to the firms' strategic CSR activities. Findings: Analysis of the data detected eight resources (i.e. investor funds, customer deposits, knowledge management processes, strategic partnerships, organisational culture, management information systems, market differentiation and supply-chain influence) and nine capabilities underpinning best-practice strategic CSR activities in the finance industry setting. In addition to these, the data indicated: the importance of managing the interdependencies that exist between the resource; the critical nature of knowledge management processes; the importance of supply-chain relationships; and the appropriateness of the RBV in strategic CSR research. Research limitations/implications: First, the data gathered for this study were from the sample organisations' annual reports only. Second, this study is based on a small sample size. Third, the qualitative approach supported the generation of results not readily generalisable. Future research should: seek to gather secondary data from a range of organisation publications; collect and analysis primary data; adopt longitudinal research methodologies to explore interactions between combinations of resources and capabilities; adopt quantitative research designs into establish the nature of any causal relationships; could replicate the method adopted in this study into a range of other industry settings. Practical implications: The findings of this study also suggest three practical implications. First, the interdependent nature of the resources deployed by the sample organisations suggests that the effective management of any one of the sustainability criteria necessitates the effective management of the other two. Second, there appears an opportunity for organisations seeking to improve their sustainability performance to develop a dedicated sustainability information system. Third, the findings in this study demonstrated an emphasis on social sustainability outcomes, which suggests that social sustainability measures are of greater relevance (or a closer "fit") with what society expects from credit providers in the finance industry. Originality/value: This paper advances the empirical and theoretical development of the strategic CSR concept by applying the RBV as a lens. This paper contributes a model of the relationship between antecedent resources and capabilities and strategic CSR, and provides guidance on the future application of the RBV in this regard.